Liminal Spaces of Memory and Remembrance: Realignment of Agonistic Interpretations at Sites of Complex Histories in Sarajevo - Ćatović Hughes, Selma; Tanović, Sabina (Brill, 2026)
This chapter explores two challenging heritage sites in Sarajevo, Bosnia and Herzegovina: the Vraca Memorial Park and the Azići-Otes battlefield. The Vraca Memorial Park is a Yugoslav memorial site dedicated to the 11,000 people who died during Axis terror in the Second World War. However, it was later used as a platform for violence during the 1990s war, making it a site of contention and liminality between the park’s historical significance and its complicated socio-political context. The Azići-Otes battlefield was a crucial place of resistance during the 1992–1996 Siege of Sarajevo, where all three ethnic groups fought in a small area, rendering it a complex and highly important strategic point in the defence of Sarajevo. Today, however, the once significant site has been forgotten and unmarked, with no trace that it was once an important location during the city’s collective resistance.
This chapter aims to shed light on how memories of these disputed territories intermingle by looking at official historical narratives and individual experiences and memories. The chapter uses an autoethnographic approach, contextualising the Azići-Otes site as a place embedded in personal family narratives and a series of somatographic sediments of traces. The collection of narrative accounts, sourced independently as oral testimonies and through the International Criminal Tribunal for the former Yugoslavia archives of witness statements, provide insights into a fragmented collective memory and the persistent development of altered narratives over the past thirty years. These individual memory retrievals begin to unpack and reconstruct composites of carefully orchestrated narratives suited for political frameworks, as well as challenge competing agendas for national remembrance and post-conflict identity. The chapter also explores the Vraca Memorial Park through the analysis of conceptual design proposals and civilian activism that call for a restoration of significance and re-activation of Vraca as both a public space and space of remembrance. These sites serve as fruitful examples for understanding disputed territories in the contemporary Balkans.
Pathways to Agonism: Disputed Territories and Memory